COVID‐19 risk mitigation behaviors among rural and urban community‐dwelling older adults in summer, 2020. Issue 3 (7th June 2021) - Probst, Janice C.; Crouch, Elizabeth L.; Eberth, Jan M.
Abstract: Purpose: Risk mitigation behaviors are important for older adults, who experience increased mortality risk from COVID‐19. We examined these reported behaviors among rural and urban community‐dwelling adults aged 65 and older. Methods: We analyzed public use files from the National Health and Aging Trends Study, which fielded a COVID survey from June to October, 2020, restricted to community‐dwelling adults (n = 2, 982). Eight behaviors were studied: handwashing, avoid touching face, mask wearing, limiting shopping, avoiding restaurants or bars, limiting gatherings, avoiding contact with those outside the household, and distancing. Residence was defined as urban (metropolitan county) or rural (nonmetropolitan county). Difference testing used Chi Square tests, with an alpha level of P = .05. Multivariable logistic regression was used to calculate adjusted odds ratios. Results: Rural residents constituted 18.8% (± Standard Error 3.6%) of the study population. In bivariate comparisons, rural older adults were less likely to report 5 of 8 studied behaviors: keep 6‐foot distance (rural: 88.3% ±1.0%, urban 93.2% ±.08%), limit gatherings (rural 87.5% ±1.8%; urban 91.6% ±0.8%), avoid restaurants/bars (rural 85.3% ±1.9%, urban 89.6% ±0.8%), avoid touching face (rural 83.1% ±2.3%, urban 88.6%, 0.8%), and avoid contact with those outside the household (rural 80.4% ±2.4%, urban 86.2% ±1.0%). After adjusting for demographic characteristics, only maintaining a 6‐foot distance remained lower among rural older adults (AOR 0.58, 95% CI: 0.42‐0.81). Conclusions: Within older adults, reported compliance with recommended behaviors to limit the spread of COVID‐19 was high. Nonetheless, consistent rural shortfalls were noted. Findings highlight the need for rural‐specific messaging strategies for future public health emergencies.